Evaluating a Novel 3D Stereoscopic Visual Display for Transanal Endoscopic Surgery: A Randomized Controlled Crossover Study. Issue 1 (January 2016) - Di Marco, Aimee N.; Jeyakumar, Jenifa; Pratt, Philip J.; Yang, Guang-Zhong; Darzi, Ara W.
Abstract : Objective: To compare surgical performance with transanal endoscopic surgery (TES) using a novel 3-dimensional (3D) stereoscopic viewer against the current modalities of a 3D stereoendoscope, 3D, and 2-dimensional (2D) high-definition monitors. Background: TES is accepted as the primary treatment for selected rectal tumors. Current TES systems offer a 2D monitor, or 3D image, viewed directly via a stereoendoscope, necessitating an uncomfortable operating position. To address this and provide a platform for future image augmentation, a 3D stereoscopic display was created. Methods: Forty participants, of mixed experience level, completed a simulated TES task using 4 visual displays (novel stereoscopic viewer and currently utilized stereoendoscope, 3D, and 2D high-definition monitors) in a randomly allocated order. Primary outcome measures were: time taken, path length, and accuracy. Secondary outcomes were: task workload and participant questionnaire results. Results: Median time taken and path length were significantly shorter for the novel viewer versus 2D and 3D, and not significantly different to the traditional stereoendoscope. Significant differences were found in accuracy, task workload, and questionnaire assessment in favor of the novel viewer, as compared to all 3 modalities. Conclusions: This novel 3D stereoscopic viewer allows surgical performance in TES equivalent to that achieved using the current stereoendoscope and superior to standard 2D and 3D displays, but with lower physical and mental demands for the surgeon. Participants expressed a preference for this system, ranking it more highly on a questionnaire. Clinical translation of this work has begun with the novel viewer being used in 5 TES patients.